Madagascar - The Third Social Fund Project - Mohan, P.C. (World Bank, Washington, DC, 2012)
The project ($ 15 million plus another $18 million - 1999-2003 ) had four objectives: (i) improved access of poor rural populations to social and economic infrastructure; (ii) on a pilot basis, empowerment of poor rural communities and/or communes to identify, organize, manage funds and implement sub-projects responsive to community needs; (iii) employment creation; and (iv) increased capacity of the private sector, local small contractors, artisans, skilled labor, and NGOs. Madagascar was struck by a series of cyclones that damaged basic infrastructure over the first three months of 2000. As part of the multi-pronged approach to assist the country in its rehabilitation efforts, in July 2000, the World Bank's Board approved a Supplemental Credit of $18 million - there was no change, however, in the project's original objectives.